Sand fly-associated phlebovirus with evidence of neutralizing antibodies in humans and dogs in Kosovo - Kurum, Elif; Jakupi, Xhevat; Xhekaj, Betim; Platzgummer, Katharina; Hoxha, Ina; Walochnik, Julia; Dvorák, Vít; Hajdari, Donjeta; Abazi, Pranvera; Obwaller, Adelheid G; Stefanovska, Jovana; Cvetkovikj, Aleksandar; et al. (Emerging microbes & infections, 2026)
The Balkan Peninsula is a hotspot for sand fly-borne phleboviruses (SbPVs), yet Kosovo had no confirmed viral detection invectors despite serological evidence of human and animal exposure. This study reports the discovery, genetic characterization, and seroprevalence of a novel phlebovirus, Grapi virus (GRPV), in Kosovo. Entomological surveys (2022-2023) collected 3,575 sand flies across seven districts. Morphological and molecular identification revealed Phlebotomus perfiliewi as the dominant species. Pan-phlebovirus RT-PCR screening identified GRPV in seven pools. Complete genome sequencing confirmed its tripartite genome, sharing 97.55-98.70% nucleotide identity with Bregalaka virus, classifying it within the Phlebovirus adanaense species. Phylogenetic analysis revealed segment-specific ancestry, suggesting recombination events between Bregalaka virus, Adana virus, and Medjerda Valley virus. Seroprevalence studies using neutralization assays detected GRPV-specific antibodies in 13.0% of humans and 2.7% of dogs. Human seropositivity peaked in adolescents and declined with age, while dogs showed higher rates in purebred and unhealthy ones. No cross-reactivity with Toscana or Sicilian viruses was observed, indicating distinct immunological responses. GRPV replicated efficiently in Vero cells and more slowly in mosquito cells, suggesting mammalian adaptation. GRPV detection in Kosovo underscores the role of the Balkan region in SbPV emergence. GRPV zoonotic potential is supported by the anthropophilic feeding behaviour of Ph. perfiliewi and by the significant seroprevalence rates in dogs and humans. Limitations include biased human/dog sampling and sparse northern Kosovo coverage. Investigating GRPV pathogenicity and ecology; integrated surveillance and diagnostics are essential for the future.
Keywords: séroepidemiologické studie; protilátky virové; mladý dospělý; Phlebovirus; Adolescent; bunyavirales; Kosovo; nemoci psů; dítě; Humans; genom virový; Male; arbovirus; Genome, Viral; fylogeneze; Antibodies, Neutralizing; Aged; Dog Diseases; Child; lidé středního věku; ženské pohlaví; Seroepidemiologic Studies; mužské pohlaví; dospělí; Antibodies, Viral; Adult; sandfly-borne phleboviruses; Middle Aged; mladiství; lidé; psi; neutralizující protilátky; senioři; Animals; Young Adult; Psychodidae; Republic of Kosovo; Phylogeny; zvířata; Female; Dogs